The ISM around WR Stars: WR152 and WR153ab - Cappa, Cristina Elisabeth (2008)
We analyze the distribution of interstellar matter in the environs of the WR stars WR 152 and WR 153ab, associated with two different ring nebulae in the H ii region Sh2-132. We have detected the radio continuum and infrared counterparts of the inner and outer ionized shells related to WR 152. An H i interstellar bubble was also identified surrounding the outer shell. As for WR 153ab, dust and molecular gas was found to be associated with its ring nebula. The emission in MSX band A suggests the presence of a photodissociation region at the interface between the ionized and molecular material.